Solution of differential equations using sum of exponential functions - Bikulčienė, Liepa; Navickas, Zenonas (Lietuvos matematikos rinkinys, 2004)
In this paper algorithm for the expression power series to sum of exponential functions are presented. The results in case of operator solving method for differential equations are applied.